Implementasi Manajemen Mutu ISO 9001:2015 Dalam Meningkatkan Mutu Sarana Dan Prasarana di Sekolah - Rumina (TABYIN: JURNAL PENDIDIKAN ISLAM, 2021)
A good management process when there are operative managerial activities. Efforts to improve the quality of school services are reflected in the application of management theory and management systems and education systems that are more micro, which can touch the overall needs of schools. Good school management is management that focuses on improving quality issues and with international standards such as ISO 9001:2015. This standard is a means to achieve quality objectives in implementing total quality control which is expected to be able to respond to developments in the era of globalization and the ultimate goal is to achieve effectiveness and efficiency of an organization. The benefits of using ISO 9001:2015 quality management are Increasing customer trust and satisfaction through organized and systematic quality assurance, Organizations that have been certified ISO 9000 are allowed to advertise that the company's quality has been internationally recognized, Quality audits which are part of ISO 9000 tasks do not need to be carried out again by the organization, and the organization's operations can be more effective and efficient. Management of facilities and infrastructure is the basis for carrying out school functions that aim to provide facilities and services in a professional manner in the field of facilities and infrastructure. An advantage for madrasas that have complete facilities and infrastructure. First, the completeness of facilities and infrastructure can lead to passion and motivation of teachers to teach. Second, the completeness of facilities and infrastructure can provide choices for students to learn.